2020
DOI: 10.1590/1808-1657000372019
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide management in glyphosate and sulfonylurea-tolerant soybeans

Abstract: There is little information on the efficacy and selectivity of sulfonylureas, isolated and in association with glyphosate, in glyphosate and sulfonylurea-tolerant soybeans. Thus, the present study aims to evaluate the efficacy of weed control and selectivity of sulfonylureas, isolated and in association with glyphosate, at post-emergence (V4) of RR2/STS soybean. The experiments were conducted in the in areas located in Piracicaba City, São Paulo State (SP), Brazil (experiment I) and Palotina City, Paraná State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…However, given the subsequent increase in glyphosate (Roundup)-resistant weeds, there has been a renewed interest in SU tolerance to be "stacked" with glyphosate resistance in soybeans. Silva et al (2020a) demonstrated that when applied postemergence and in combination with glyphosate herbicide, SU herbicides (sulfometuron, chlorimuron, halosulfuron, and ethoxysulfuron) provide effective weed management in the STS cultivar BMX Garra RR2/STS and improved yield. W20 lines homozygous for the tolerant allele at the ALS1 locus were subject to a second round of mutagenesis (Walter et al, 2014).…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given the subsequent increase in glyphosate (Roundup)-resistant weeds, there has been a renewed interest in SU tolerance to be "stacked" with glyphosate resistance in soybeans. Silva et al (2020a) demonstrated that when applied postemergence and in combination with glyphosate herbicide, SU herbicides (sulfometuron, chlorimuron, halosulfuron, and ethoxysulfuron) provide effective weed management in the STS cultivar BMX Garra RR2/STS and improved yield. W20 lines homozygous for the tolerant allele at the ALS1 locus were subject to a second round of mutagenesis (Walter et al, 2014).…”
Section: Core Ideasmentioning
confidence: 99%
“…Silva et al. (2020a) demonstrated that when applied postemergence and in combination with glyphosate herbicide, SU herbicides (sulfometuron, chlorimuron, halosulfuron, and ethoxysulfuron) provide effective weed management in the STS cultivar BMX Garra RR2/STS and improved yield.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar da boa performance apresentada pelo ethoxysulfuron no controle de soja voluntária, é oportuno destacar que o uso deste herbicida com esta finalidade pode apresentar restrições quanto ao controle em se tratando de cultivar de soja contendo em sua base genética a tecnologia STS, uma vez que para estes materiais há uma tolerância aos herbicidas do grupo químico das sulfonilureias (SILVA et al 2020). Desta forma, recomenda-se que os técnicos vinculados ao setor agrícola que optarem pela utilização do ethoxysulfuron com o propósito de controlar a soja voluntária tenham o conhecimento da genética da cultivar de soja antes de recomendar a aplicação do herbicida.…”
Section: Uso De Ethoxysulfuron Visando O Controle De Soja Voluntária ...unclassified